Stability Assessment of Dangerous Rock Mass of an Overhanging Slope in Puerdu Town, Southwestern China - Wen-Lian Liu; Jia-Xing Dong; Su-Gang Sui; Han-Hua Xu; Run-Xue Yang; Zhen-Luo Shen (Advances in Civil Engineering)
Dangerous rock mass in the overhanging slope of Puerdu town has good free-face condition, high position, and great potential energy, identification and stability evaluation of which is a difficult problem in the disaster prevention. In this paper, the limit equilibrium method was used to evaluate the dangerous rock mass stability in the overhanging slope. Firstly, geomorphic characteristics and the distribution of dangerous rock mass are determined by the field geological survey. Secondly, six dangerous rock masses which may cause more threat are studied, with defining their failure modes and characteristic parameters. Finally, a simplified geological model is established, the stability coefficient of dangerous rock mass under different conditions is calculated by the limit equilibrium method, at the same time, stability analysis of dangerous rock mass is carried out based on the stereographic projection, and the hazard probability is estimated by the empirical formula. Results show that joints obviously developed in the dangerous rock mass of W1, W2, W3, W4, W5, and W6, with falling-type and toppling-type failure modes. In the natural condition, the dangerous rock mass is understable and unstable under the rainstorm and earthquake conditions. Consequently, rainstorm and earthquake are the key triggering factors of the instability and collapse of dangerous rock mass.